The Relationship Between Work Stress and the Work Productivity of Openwork Craftsmen in Mongolato Village, Telaga District, Gorontalo Regency - Sheinta Inado; Rona Febriyona; Andi Nur Aina Sudirman (Universitas Ibn Khaldun Bogor, 2023)
Work stress is a condition that exceeds the limits of an individual's ability, where the individual is unable to do his job. The purpose of this study was to determine the relationship between work stress and work productivity of openwork craftsmen in Mongolato Village, Telaga District, Gorontalo Regency. This type of research uses quantitative research methods with a cross-sectional design. The population in this study amounted to 84 respondents, with a total sampling sample technique. The research instrument used a questionnaire with a statistical test, namely Chi-Square. The results showed a relationship between work stress and the work productivity of openwork craftsmen and obtained P Value = 0.005 < 0.05. Based on the results of the analysis of 84 respondents, it is known that filigree craftsmen who experience moderate work stress with work productivity as many as 17 respondents, of which 6 respondents with sufficient productivity, and 11 respondents with good work productivity. Craftsmen who experienced severe work stress with work productivity were 67 respondents, of which 48 respondents with sufficient work productivity, and 19 respondents with good work productivity. The study concludes that there is a relationship between work stress and work productivity. Openwork craftsmen should routinely do recreation together, always be compact in doing work to reduce work stress, and always maintain accuracy, neatness, and always maintain discipline in work so that it can further increase work productivity.